Effects of different crop rotation patterns on the growth of Guizhou sorghum and rhizosphere soil quality: implications for agricultural policy - Chen, Manjing; Shen, Jiaqi; Zhao, Ying; Xie, Peiyun; Zhou, Yingying; Jiang, Yuwen; Deng, Xiaofeng; Ren, Yan; Shao, Mingbo (Frontiers in Microbiology, 2025)
IntroductionSorghum, an important crop for food and raw material for Baijiu production, is typically cultivated using monocropping. However, the impact of long-term sorghum monocropping on soil physicochemical properties and microbial communities is poorly elucidated. Hence, this study was conducted to evaluate the effects of different crop rotation patterns on sorghum growth and the soil microenvironment in Guizhou Province, China.MethodsFollowing a randomized block design, the effects of three cropping patterns, continuous sorghum cropping (SSS), sorghum–rapeseed–sorghum (SRS), and sorghum–stem mustard–sorghum (SMS), on sorghum yield, rhizosphere soil quality, and soil microbial community structure were compared.ResultsCompared with the SSS treatment, the SRS and SMS treatments significantly improved the agronomic traits of sorghum as well as the physicochemical traits of soil. Among the treatments, urease and invertase activities were the highest in SRS. Moreover, compared with the SSS treatment, the SRS and SMS treatments significantly altered the composition of the rhizosphere microbial community by reducing the abundance of pathogenic phyla. Furthermore, correlation analysis revealed that soil organic matter, total potassium, available potassium, available phosphorus, and invertase activity are key environmental factors influencing the soil microbial community structure.DiscussionSorghum rotation with other crops, such as rapeseed and stem mustard, can improve the soil microenvironment, regulate the soil microbial community structure, alleviate continuous cropping obstacles, and enhance sorghum quality and yield. This finding highlights the importance of optimizing crop rotation patterns to alleviate continuous cropping obstacles.